Some notes on the Semerap dialect of Kerinci and its historical development - Ernanda, Ernanda (Wacana, Journal of the Humanities of Indonesia, 2021)
This article investigates the historical development of a hitherto undescribed Kerinci variety, the Semerap dialect, from a comparative Malayic perspective. The morphophonological characteristics of Kerinci languages are unusual within the Austronesian language family. This preliminary study, therefore, pays special attention to the characteristic four-way split of the historical root- final *V(C)# in Semerap lexemes: absolute, oblique, K-words, and G-words. Like other Kerinci varieties, the Semerap dialect features a type of phonological word-shape alternation, generally known as “phrasal alternation”, which also impacts on its syntax. This alternation (absolute vs. oblique) is determined by the syntactic position of the root, but also by semantic factors. To gain an accurate understanding of Semerap historical development, I also call attention to non- prenasalized voiced stops (G-phonemes), which also influence the realization of the root-final *V(C)#. Finally, an argument is made to take Kerinci varieties into account for Malay historical linguistics more generally.